2007
DOI: 10.1007/s11207-007-9042-2
|View full text |Cite
|
Sign up to set email alerts
|

Solar Cycle Variation of the Interplanetary Forward Shock Drivers Observed at 1 AU

Abstract: Forecasting space weather more accurately from solar observations requires an understanding of the variations in physical properties of interplanetary (IP) shocks as solar activity changes. We examined the characteristics (occurrence rate, physical parameters, and types of shock driver) of IP shocks. During the period of 1995 -2001, a total of 249 forward IP shocks were observed. In calculating the shock parameters, we used the solar wind data from Wind at the solar minimum period (1995 -1997) and from ACE si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 24 publications
5
48
1
Order By: Relevance
“…Moreover, the shock frequency has a cycle dependence closely related with the yearly mean sunspot number (see Fig. 2 of Oh et al 2007). A very similar frequency dependence is found for ICMEs (Robbrecht et al 2009;Boursier et al 2009).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Moreover, the shock frequency has a cycle dependence closely related with the yearly mean sunspot number (see Fig. 2 of Oh et al 2007). A very similar frequency dependence is found for ICMEs (Robbrecht et al 2009;Boursier et al 2009).…”
Section: Introductionsupporting
confidence: 65%
“…At 1 AU and with in situ data, Berdichevsky et al (2000) found that only 43% (18/42) of shocks are associated to ICMEs during a solar minimum period (1994−1997). Analyzing seven years of data with Wind and ACE, Oh et al (2007) found that 79% (196/246) of shocks are associated to ICMEs (MCs and ejecta), while 21% (40/246) of shocks are associated to CIRs (or high speed streams, HSS). Moreover, the shock frequency has a cycle dependence closely related with the yearly mean sunspot number (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The larger values for our control sample may be due to the fact that it includes more shocks during the rise and solar maximum phases (1999–2002) than a random sample would have. Shocks at solar maximum tend to be faster and have larger Mach numbers and compression ratio [ Oh et al , ]. This may also reflect the fact that this sample excludes shocks inside CMEs which tend to have lower compression ratio and Mach numbers, as discussed below.…”
Section: Upstream Conditions and Properties Of Shocks Inside Cmesmentioning
confidence: 99%
“…Certainly, CMEs play a very important role in formation of the coronal waves (Biesecker et al, 2002), and most of the interplanetary shocks are driven by CMEs (Reiner et al, 2001;Oh, Yi, and Kim, 2007). However, it remains unclear whether coronal shocks are CME driven (Cliver et al, 2004) or flare ignited (Vršnak, 2001).…”
Section: Introductionmentioning
confidence: 99%